2011
DOI: 10.1095/biolreprod.110.088591
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Fluid Regulates Accumulation of FOXP3+ Regulatory T Cells in the Preimplantation Mouse Uterus Through Expanding the FOXP3+ Cell Pool and CCL19-Mediated Recruitment1

Abstract: Regulatory T (Treg) cells facilitate maternal immune tolerance of the semiallogeneic conceptus in early pregnancy, but the origin and regulation of these cells at embryo implantation is unclear. During the preimplantation period, factors in the seminal fluid delivered at coitus cause expansion of a CD4(+)CD25(+) putative Treg cell population in the para-aortic lymph nodes draining the uterus. Using flow cytometry, immunohistochemistry, and real-time quantitative PCR (qPCR) for the signature Treg cell transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
175
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(188 citation statements)
references
References 57 publications
10
175
2
1
Order By: Relevance
“…This is consistent with previous encounter and priming to seminal fluid Ags, which would be expected in sexually active women not using barrier contraception. This contrasts with experiments in virgin mice, where reproductive tract T cells are less abundant and seminal fluid-induced population expansion requires several days to become detectable (14,34). Notwithstanding the more rapid and predominantly memory T cell response we observed in women, the time frame of this study is not ideal for detecting T cell responses, which generally take .12 h to fully evolve.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…This is consistent with previous encounter and priming to seminal fluid Ags, which would be expected in sexually active women not using barrier contraception. This contrasts with experiments in virgin mice, where reproductive tract T cells are less abundant and seminal fluid-induced population expansion requires several days to become detectable (14,34). Notwithstanding the more rapid and predominantly memory T cell response we observed in women, the time frame of this study is not ideal for detecting T cell responses, which generally take .12 h to fully evolve.…”
Section: Discussioncontrasting
confidence: 60%
“…Based on our findings in mice (12,14), we speculate that cervical T cells play a crucial role in the development of tolerogenic immune responses to male transplantation Ags contained within the ejaculate. The phenotype of any T cell response is relevant to the fate of sperm and, thus, future fertility.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Initial studies depleting T-regulator lymphocytes showed a failure of pregnancy due to immune rejection of the conceptus [89]. Our studies have now shown that exposure to seminal plasma at insemination drives expansion of T-regulatory lymphocytes in the PALN and uterus [90].…”
Section: Lymphocyte Activation Following Inseminationmentioning
confidence: 62%
“…Sex itself might be a part of the answer. In a mouse model, seminal fluid regulates the accumulation of Treg at the FGT [130]. Semen contains high concentrations of TGF-b [114,115,131] and exposure to seminal plasma converts naïve T cells into functional FOXP3-negative Treg that secrete TGF-b [132].…”
Section: Regulatory T Cells and Immunoregulation At The Fgtmentioning
confidence: 99%